2017
DOI: 10.3389/fmicb.2017.01089
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Microbiome along the Gastrointestinal Tract of Growing Turkeys

Abstract: The turkey microbiome is largely understudied, despite its relationship with bird health and growth, and the prevalence of human pathogens such as Campylobacter spp. In this study we investigated the microbiome within the small intestine (SI), caeca (C), large intestine (LI), and cloaca (CL) of turkeys at 6, 10, and 16 weeks of age. Eight turkeys were dissected within each age category and the contents of the SI, C, LI, and CL were harvested. 16S rDNA based QPCR was performed on all samples and samples for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
64
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 40 publications
12
64
2
Order By: Relevance
“…LEfSe analyses showed that the Clostridiaceae family (Firmicutes phylum) is abundant in the lower intestine of granivorous birds and Clostridium genus is predominant in the gizzard and upper intestine in frugivorous birds ( Fig 4D, 4E and 4F ), particularly in Buff-throated Saltator ( Fig 2 ). This family of bacteria is abundant in the ceca of granivorous chicken [ 13 , 28 ], neotropical birds [ 6 ], gastrointestinal tract of turkeys [ 29 ] and in vulture facial skin and hindgut samples [ 14 ]. The members of this bacterial family are associated with proteolytic activity and complex carbohydrate degradation, [ 30 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…LEfSe analyses showed that the Clostridiaceae family (Firmicutes phylum) is abundant in the lower intestine of granivorous birds and Clostridium genus is predominant in the gizzard and upper intestine in frugivorous birds ( Fig 4D, 4E and 4F ), particularly in Buff-throated Saltator ( Fig 2 ). This family of bacteria is abundant in the ceca of granivorous chicken [ 13 , 28 ], neotropical birds [ 6 ], gastrointestinal tract of turkeys [ 29 ] and in vulture facial skin and hindgut samples [ 14 ]. The members of this bacterial family are associated with proteolytic activity and complex carbohydrate degradation, [ 30 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have used high-throughput sequencing to investigate the gut microbial diversity of poultry. Among them, sequencing the rRNA gene of a gut microbiome is relatively simple and cost-effective, nonetheless understanding the function of the microbiome is key for understanding interrelationships with the host (Wilkinson et al 2017). In this study, we used an Illumina MiSeq approach to investigate bacterial community diversity within the duodenum (S), jejunum (K) and caecum (M) contents of 30-week-old (peak production stage) Jinghong laying hens.…”
Section: Discussionmentioning
confidence: 99%
“…16S rRNA gene sequences were processed as described by Wilkinson et al (2017) . Essentially, the CD-HIT-OTU pipeline ( Li et al, 2012 ) was used to denoise the sequences and remove low quality sequences, pyrosequencing errors and chimeras.…”
Section: Methodsmentioning
confidence: 99%